Synthetic Approaches for (15)N-labeled Hyperpolarized Heterocyclic Molecular Imaging Agents for (15)N NMR Signal Amplification By Reversible Exchange in Microtesla Magnetic Fields - Chukanov, Nikita V. (Chemistry, 2021)
NMR hyperpolarization techniques enhance nuclear spin polarization by several orders of magnitude resulting in corresponding sensitivity gains. This massive sensitivity gain enables new applications ranging from studies of small molecules using high-resolution NMR spectroscopy to real-time metabolic imaging in vivo. Several hyperpolarization techniques exist for hyperpolarization of a large repertoire of nuclear spins, although (13)C- and (15)N- sites of biocompatible agents are the key targets due to their widespread in biochemical pathways. Moreover, their long T(1) allows retaining hyperpolarized states for up to tens of minutes. Signal Amplification by Reversible Exchange (SABRE) is a low-cost and ultrafast hyperpolarization technique that has been shown to be versatile for hyperpolarization of (15)N nuclei. While large sensitivity gains are enabled by hyperpolarization, (15)N natural abundance is only ~0.4%, so that isotopic labeling of the to-be-hyperpolarized molecules is required in order to take full advantage of the hyperpolarized state. Here, we describe selected advances in the preparation of (15)N-labeled compounds with the primary emphasis on using these compounds for their SABRE polarization in microtesla magnetic fields via spontaneous polarization transfer from parahydrogen. Also, these principles can certainly be applied for hyperpolarization of these emerging contrast agents using Dynamic Nuclear Polarization and other techniques.